Improving access to primary mental healthcare for Indigenous Australians. (February 2015) - Reifels, Lennart; Bassilios, Bridget; Nicholas, Angela; Fletcher, Justine; King, Kylie; Ewen, Shaun; Pirkis, Jane
Objective: To examine the uptake, population reach and outcomes of primary mental healthcare services provided to Indigenous Australians via the Access to Allied Psychological Services (ATAPS) program between 2003 and 2013, with particular reference to enhanced Indigenous ATAPS services introduced from 2010. Method: Utilising ATAPS program data from a national minimum data set and comparative population data, we conducted descriptive analyses, regression analyses and t-tests to examine the uptake of ATAPS services, provider agency level predictors of service reach, and preliminary outcome data on consumer level outcomes. Results: Between 2003 and 2013, 15, 450 Indigenous client referrals were made that resulted in 55, 134 ATAPS sessions. National Indigenous service volume more than doubled between 2010 and 2012, following the introduction of enhanced Indigenous ATAPS services. Non-Indigenous ATAPS service volume of primary care agencies was uniquely predictive of Indigenous service reach. Preliminary analysis of limited consumer outcome data indicated positive treatment gains and the need to enhance future outcome data collection. Conclusions: Concerted national efforts to enhance mainstream primary mental healthcare programs can result in significant gains in access to mental healthcare for Indigenous populations.